OPTIMIZING SHARIA ECONOMICS PRINCIPLES IN STATE LAW FOR ENHANCED VILLAGE GOVERNANCE: A CASE STUDY OF ALUH-ALUH VILLAGE, BANJAR REGENCY - Bahran, Bahran; Sulistyoko, Arie; Hafidzi, Anwar; Nadiyah, Nadiyah (Universitas Muhammadiyah Surabaya, 2024)
This study aims to explore how the optimization of the application of Sharia-based State Law can enhance the quality of village governance, with a focus on Aluh-Aluh Village in Banjar Regency. The application of Sharia-based State Law is expected to improve the mechanisms and processes of village governance and integrate Sharia principles into resource management and public services. The research employs a qualitative approach, with data collected through interviews with village officials, observation of activities, and document studies. The findings indicate that the application of Sharia economic principles, such as justice ('adl), transparency (shafafiyah), and social responsibility (mas'uliyah), not only enhances transparency and accountability within village governance but also strengthens community participation in decision-making and resource management. Integrating these principles offers solutions to challenges such as unequal resource distribution, low transparency, and weak accountability. The implications of this research suggest that the implementation of Sharia-based State Law can promote more responsible financial management practices, increase community involvement, and support sustainable development. The integration of Sharia economic principles into village governance provides a model for other villages with similar conditions and can enhance community engagement and public service quality. The study recommends long-term planning and adherence to Sharia principles to improve transparency, accountability, and prosperity at the village level.